Lactobacillus as a Probiotic Feed for Chickens - Raja, M. Mohamed Mahroop; Raja, A.; Imran, M. Mohamed (International Journal of Poultry Science, 2009)
The present study was carried out to isolate and identify microorganisms as a probiotic feed for chicken. The strains were isolated from gut region of the chick and was inoculated in to the MRS Medium and incubated at 37oC for 48 h under anaerobiosis. The identity of culture was based on the characteristics of Lactobacilli as presented in the Bergey’s Manual of Determinative Bacteriology using Gram Staining, Motility, Triple Sugar Iron and Fermentation of different carbon sources. Based on the criteria Lactobacillus fermentum tolerated on Inhibitory substances, Temperature and agitation were identified and tested for probiotic use for chickens. Lactobacillus fermentum shows antimicrobial activity and shows the similar effects to antibiotic in the feed. It could be a suitable strain as a probiotic feed for chickens.